2022
DOI: 10.3390/insects13010104
|View full text |Cite
|
Sign up to set email alerts
|

Decoyinine Induced Resistance in Rice against Small Brown Planthopper Laodelphax striatellus

Abstract: Induced resistance against SBPH via microbial pesticides is considered as an eco-friendly and promising management approach. In this study, the induced resistance against SBPH in rice seedling by a new potential microbial pesticide, decoyinine (DCY), a secondary metabolite produced by Streptomyces hygroscopicus, was evaluated to investigate the effects of DCY on SBPH’s biological and population parameters along with defense-related physiological and biochemical indices in rice against SBPH feeding. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Recently, a growing body of evidence has suggested that GV also fortifies plants against pest damage (Figure ). Priming rice seeds with GV has been found to enhance resistance to brown planthopper (BPH, Nilaparvata lugens) and small brown planthopper (SBPH, Laodelphax striatellus) by significantly reducing their fertility. Physio-biochemical analyses indicate that when GV-treated rice was fed upon by BPH, there was an enhancement in the activities of plant defense-related enzymes including superoxide dismutase (SOD), catalase (CAT), glutathione S transferase (GST), peroxidase (POD), and polyphenol oxidase (PPO) . Additionally, transcriptomic analyses showed that these feeding events precede the upregulation of 15 resistance-related WRKY genes.…”
Section: Effect Of Guvermectin On Plant Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Recently, a growing body of evidence has suggested that GV also fortifies plants against pest damage (Figure ). Priming rice seeds with GV has been found to enhance resistance to brown planthopper (BPH, Nilaparvata lugens) and small brown planthopper (SBPH, Laodelphax striatellus) by significantly reducing their fertility. Physio-biochemical analyses indicate that when GV-treated rice was fed upon by BPH, there was an enhancement in the activities of plant defense-related enzymes including superoxide dismutase (SOD), catalase (CAT), glutathione S transferase (GST), peroxidase (POD), and polyphenol oxidase (PPO) . Additionally, transcriptomic analyses showed that these feeding events precede the upregulation of 15 resistance-related WRKY genes.…”
Section: Effect Of Guvermectin On Plant Biotic and Abiotic Stressesmentioning
confidence: 99%
“…An earlier study indicated that treating rice seedlings by root drenching with Bacillus velezensis YC7010, an endophytic strain, induced systemic resistance against BPH ( Harun-Or-Rashid et al, 2018 ). Another study reported the efficiency of decoyinine, a metabolite derived from the endophytic Streptomyces hygroscopicus in triggering induced systemic resistance in rice against the SBPH, L. striatellus and indirectly affect the fecundity and population life table parameters ( Shah et al, 2022 ).…”
Section: Roles Of Microbiota and Srnas In Ricementioning
confidence: 99%
“…Previous studies have shown that antioxidant enzymes, such as POD, SOD, CAT, and PPO, are involved in plant defense [31,32], therefore, we tested the activities of POD, SOD, CAT, and PPO after exogenously application of various concentrations of serotonin. The POD activities were significantly higher in serotonin-treated rice plants, reaching highest activities at concentrations of 50 and 100 µM, compared to control plants (Figure 7A).…”
Section: Exogenous Serotonin Affects the Activities Of Antioxidant En...mentioning
confidence: 99%
“…Previous studies have demonstrated that nutrient constituents, such as soluble sugars and free amino acids, are important indexes of host plant quality and are associated with BPH-induced rice defense [29,30]. In addition, the role of flavonoids, and defensive proteins including peroxidase (POD), superoxide dismutase (SOD), catalase (CAT), and polyphenol oxidase (PPO) in regulating rice resistance to BPH has also been well documented [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%